Radiation dose to radiosensitive organs in PET/CT myocardial perfusion examination using versatile optical fibre - Salasiah, M.; Nordin, A.J.; Fathinul Fikri, A.S.; Hishar, H.; Tamchek, N.; Taiman, K.; Ahmad Bazli, A.K.; Abdul-Rashid, H.A.; Mahdiraji, G.A.; Mizanur, R.; Noramaliza, M.N. (International Society for Optical Engineering, 2013)
Cardiac positron emission tomography (PET) provides a precise method in order to diagnose obstructive coronary artery disease (CAD), compared to single photon emission tomography (SPECT). PET is suitable for obese and patients who underwent pharmacologic stress procedures. It has the ability to evaluate multivessel coronary artery disease by recording changes in left ventricular function from rest to peak stress and quantifying myocardial perfusion (in mL/min/g of tissue). However, the radiation dose to the radiosensitive organs has become crucial issues in the Positron Emission Tomography/Computed Tomography(PET/CT) scanning procedure. The objective of this study was to estimate radiation dose to radiosensitive organs of patients who underwent PET/CT myocardial perfusion examination at Centre for Diagnostic Nuclear Imaging, Universiti Putra Malaysia in one month period using versatile optical fibres (Ge-B-doped Flat Fibre) and LiF (TLD-100 chips). All stress and rest paired myocardial perfusion PET/CT scans will be performed with the use of Rubidium-82 (82Rb). The optic fibres were loaded into plastic capsules and attached to patient’s eyes, thyroid and breasts prior to the infusion of 82Rb, to accommodate the ten cases for the rest and stress PET scans. The results were compared with established thermoluminescence material, TLD-100 chips. The result shows that radiation dose given by TLD-100 and Germanium-Boron-doped Flat Fiber (Ge-B-doped Flat Fiber) for these five organs were comparable to each other where the p>0.05. For CT scans,thyroid received the highest dose compared to other organs. Meanwhile, for PET scans, breasts received the highest dose. © (2013) COPYRIGHT Society of Photo-Optical Instrumentation Engineers (SPIE). Downloading of the abstract is permitted for personal use only.